2003
DOI: 10.1034/j.1600-0420.2003.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year risk of progression of primary angle closure to primary angle closure glaucoma: a population‐based study

Abstract: ABSTRACT.Objective: To report the 5-year progression to primary angle closure glaucoma (PACG) in a population-based cohort of primary angle closure (PAC) subjects. Methods: A total of 37 patients diagnosed as PAC during a population-based study in 1995 were invited for re-examination in 2000. Patients underwent a complete ophthalmic examination including ocular biometry. Progression to PACG was based on optic disc damage and field defects on automated perimetry. Results: In all, 28 of 32 PAC subjects who could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
138
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(144 citation statements)
references
References 20 publications
2
138
4
Order By: Relevance
“…Three broad categories: suspect, established angleclosure and angle-closure glaucoma follow our conceptual model of the natural history, and reflect prognosis for vision. [13][14][15] Within each category, there is a spectrum of severity. Narrower angles are more likely to close than wider angles.…”
Section: Definition and Classificationmentioning
confidence: 99%
“…Three broad categories: suspect, established angleclosure and angle-closure glaucoma follow our conceptual model of the natural history, and reflect prognosis for vision. [13][14][15] Within each category, there is a spectrum of severity. Narrower angles are more likely to close than wider angles.…”
Section: Definition and Classificationmentioning
confidence: 99%
“…9 Recently, Thomas et al have shown, in an Asian cohort, that 22% of primary angle closure suspects developed raised intraocular pressure (IOP) or synechiae over a 5-year period 10 and in a separate smaller group with known primary angle closure 28.5% progressed to glaucoma as evidenced by disc damage and perimetry defects over the same period. 11 Despite these studies, there is still paucity of larger studies with long-term data on the natural history of treated and untreated narrow angles, particularly among Caucasian populations.…”
Section: Introductionmentioning
confidence: 99%
“…Those with an acute, reversible event of elevated intraocular pressure should be considered as having APAC. 10 Based on this classification, manifest PACG prevalence was found to be 0.5% (95% CI 0.1-0.9%) in the VES 11 and 0.7% in the population over 30 years in the Andhra Pradesh Eye Disease Study (95% CI 0.34-1.31%). 2 These rates are comparable to studies from Singapore (0.8%) 12 and Mongolia (0.8%).…”
Section: Introductionmentioning
confidence: 99%